Longitudinal approach to publicly held and privately owned family businesses : a financial analysis - Jonkus, Edvinas (2013)
The main aim of this thesis is to examine the consequences of the 2007 financial crisis for family and non-family businesses and identify and understand what makes businesses sustainable and profitable even during bad macro-economic conditions. This financial crisis was one of the most significant since the Wall Street Crash of 1929. I will analyze selected companies’ financial statements before, during, and after 2007 financial crisis. My goal is to outline the advantages and disadvantages of family and non-family companies, and moreover, to see which ownership structure weathered the financial crisis better. The analysis in this paper is based on two companies’ financial statements comparison among 2006 and 2010. The selected enterprises are Orion, a private Finnish firm which is listed on OMX Helsinki stock exchange, and Boehringer-Ingelheim, a German family business (not listed on stock markets). Both companies operate in the pharmaceutical industry and have strong footprints in international markets.